Effect of Annealing Temperature on the Microstructure, Mechanical Properties, and Electrical Conductivity of 4xxx Series Al-Based Alloys - Mohammad Khoshghadam-Pireyousefan; Mousa Javidani; Alexandre Maltais; Julie Lévesque; X.-Grant Chen (Engineering Proceedings, 2023)
This study investigated the effects of annealing on the microstructure, mechanical properties, and electrical conductivity (EC) of AA4043 rods produced through the Properzi CCR process. Annealing was conducted at two temperatures (200 °C and 300 °C) for 4 h. Characterization techniques were performed on the rod samples, including optical microscopy, EBSD, microhardness, tensile tests, and EC measurements. The results showed a significant improvement in EC with decreased mechanical strength during annealing. The sample annealed at 300 °C exhibited the most favorable combination of EC (57.48% IACS), microhardness (41 HV), and ultimate tensile strength (124 MPa). Furthermore, the image analysis revealed slight alterations in the shape factors of eutectic Si particles with increasing annealing temperature. In addition, EBSD results demonstrated that the annealing promoted the recrystallization process.